Hematopoietic Stem Cell Transplantation for Patients with Paroxysmal Nocturnal Hemoglobinuria with or without Aplastic Anemia: A Multicenter Turkish Experience - (:unkn) unknown (GALENOS YAYINCILIK, 2021)
Objective: Although inhibition of the complement system at different steps is a promising therapy modality in patients with paroxysmal nocturnal hemoglobinuria (PNH), allogeneic hematopoietic stem cell transplantation (HCT) is still the only curative therapy, especially for patients with intractable hemolysis or bone marrow failure. The aim of this study is to evaluate the outcomes of allogeneic HCT in PNH patients with aplastic anemia (PNH-AA) or without. Materials and Methods: Thirty-five PNH/PNH-AA patients who were treated with allogeneic HCT in 10 transplantation centers in Turkey were retrospectively analyzed. Results: Sixteen (45.7%) and 19 (54.3%) patients were diagnosed with classical PNH and PNH-AA, respectively. The median age of the patients was 32 (18-51) years. The 2-year overall survival (OS) rate and rate of graft-versus-host disease-free, failure-free survival (GFFS) was 81.2% and 78.1%, respectively. The 2-year OS in cases of classical PNH and PNH-AA was 81.3% and 79.9%, respectively (p=0.87), and 2-year GFFS in cases of PNH and PNH-AA was 79% and 76% (p=0.977), without statistical significance. The OS and GFFS rates also did not differ between transplantations with matched sibling donors (MSDs) and matched unrelated donors (MUDs). Conclusion: Allogeneic HCT with MSDs or MUDS is a good option for selected patients with classical PNH and PNH-AA. In particular, patients with debilitating and refractory hemolysis and patients with bone marrow failure might form an excellent group of candidates for allogeneic HCT.
Keywords: Paroxysmal nocturnal hemoglobinuria; Transplantation; Allogeneic stem cell transplantation; Aplastic anemia; BONE-MARROW-TRANSPLANTATION; DIAGNOSIS